B90 Inter-fascial space between sartorius muscle and femoral artery – ISAFE: novel approach for adductor canal catheter – ACC. (11th August 2022) - Alekberli, T; dos Santos Fernandes, H; Siddiqui, N; Peacock, S; Vidal, E; Wolfstadt, J; Gleicher, Y
Abstract : Background and Aims: We propose the ISAFE technique for ACC placement ( Figures - 1 & 2 ) to avoid the proximity of catheter tip to Femoral Vein-FV, an accidental venous-puncture, reduce potential trauma to saphenous nerve - SN, and prevent ACC - dislodgement. Methods: ACC were inserted in sixteen total knee arthroplasty (TKA) patients postoperatively to avoid ACC displacement by the intraoperative thigh-tourniquet. 5 mL/h disposable elastomeric infusion-pump (Baxter-International-Inc., IL, US) of 250 ml- Ropivacaine 0.2% infused over 48 hours-outpatient setting. The ISAFE approach: Needle insertion : level of the mid-adductor canal, mid-sartorius, in-plane (lateral to medial) Needle advancement: piercing through the posterior fascia of Sartorius muscle-SM approximately 1–2 cm lateral to Femoral Artery-FA, entering adductor canal ( Figure 1 ). ISAFE hydro-dissection: Needle angle is then decreased to avoid FV and advanced into the inter-fascial space between FA and SM ( Figure 1 ). Hydro-dissection is necessary to open the inter-fascial space and separating FA from SM. Catheter insertionat the 11 o'clock position anteromedial position to FA, facilitating over-threading catheter (Figure-2). We recommend threading the catheter approximately 3–5 mm past FA. Results: No local-anesthetic systemic toxicity, intravascular puncture, or ACC-dislodgments was noted. 9-patients (56.25%) required NO opioid analgesia over three-day postoperative period. Mean cumulative opioid-consumption (in oral morphine-equivalent) on postoperative days- 2–3 were 10.78 ± 14.33 mg and 12.50 ± 18.68 mg, respectively. Conclusions: The ISAFE approach for ACC placement is potentially safer, feasible, and reliable for maintaining analgesia after TKA. The ISAFE technique, while feasible for practitioners in regional anesthesia, has a learning-curve and requires training.